MARKET ANALYSIS DRIVEN CONSUMER BEHAVIOR ASSESSMENT OF SELECTED FISH MARKETS IN MAHARASHTRA, INDIA - WAGHMARE, SHYAMDATTA; PRAKASH, SWADESH; SHARMA, ARPITA; YADAV, BINOD KUMAR; QURESHI, NEHA (Journal of the Inland Fisheries Society of India, 2025)
The inland fisheries is considered a sunrise sector and is poised to play a significant role in the Indian economy in the near future. With his background, the present study was undertaken to study the consumer behavior, structure, conduct & performance of selected fish markets in Maharashtra. A pre-tested interview schedule was used to collect data from fishers, traders, and consumers. The data obtained by the survey were analyzed using descriptive statistics, the Chi-Square test and Rank Based Quotient (RBQ) using MS Excel and SPSS software. The result showed that the selected fish markets are in the inland areas and deal with freshwater fish, prawns, crabs, marine, fish, and prawns. The most preferred fish species are tilapia, freshwater eel, murrel, catla, rohu, mrigal, freshwater shark, and pangas. Due to its taste and cost, tilapia constitutes almost 90% of the total catch. Marketing cost was estimated for Tilapia, IMC, freshwater eel, and Murrel fish for two different major channels. This showed that marketing cost for the first (longer) auctioneer channel, auctioneer, and wholesaler cost is ₹ 2/kg and ₹ 3/kg, respectively. The price spread was higher for IMC and murrel than freshwater eel and tilapia fish. Fish is generally perceived to be cheaper in both the selected fish markets. Most consumers reported that taste was the primary criterion for purchasing fish from the market, followed by the price of fish, and 40% of consumers were consuming fish more than twice a week. Consumer attitudes about the four pillars of food security, namely availability, accessibility (measured as affordability), quality, and stability along with other aspects of cultural and social preferences toward fish results showed that consumers in both markets were positive about the availability, accessibility, quality, and stability of fish in the market. The study identified that fluctuating prices and the unavailability of fresh fish throughout the year were major constraints faced by consumers.